Peran Pemberian Nutrisi dalam Penanganan Marasmus pada Balita The Role of Nutrition in Handling Marasmus in Toddlers - Fitriani Fitriani; Hamdan Satria; Hana Fadilah Putri (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Marasmus is a form of malnutrition that is most often found in toddlers, where the body becomes very thin and the bones appear protruding under the skin. This is caused by insufficient calorie food intake, which forces the body to constantly use its energy reserves. The aim of this research is to overcome problems in marasmus sufferers where there are various treatments that can be given, one of which is by providing knowledge to families and the community about the importance of preventive and rehabilitation measures by providing appropriate nutritional guidelines. This research is in the form of a literature review. Literature was taken from two databases, namely Pubmed and Google Scholar. After being selected using inclusion and exclusion criteria, seven pieces of literature were obtained consisting of six descriptive studies and one qualitative study. The results of the research show that seven pieces of literature examine how to treat marasmus by providing nutrition accompanied by data in the form of tables. According to data from Basic Health Research (RISKESDAS) and the National Socio-Economic Survey (SUSENAS), the results of this data show that the prevalence of malnutrition decreased from 1998 to 2001, namely in 1998-1999 it decreased by 2% and in 1999-2001 it decreased again. by 1.8%. And from 2001 to 2005 there was an increase in the prevalence of malnutrition, namely in 2001-2003 it increased by 2% and in 2003-2005 it increased again by 0.5%. Then from 2005 to 2010 it experienced another decline, namely in 2005-2007 it was 3.4% and in 2007-2010 it was 0.5%, and in 2010 to 2013 it experienced another increase of 0.8%. As a conclusion, there are various treatments to overcome this problem. However, the problem of malnutrition, including marasmus, has not been resolved and is still relatively high. Therefore, public awareness is still needed regarding the importance of providing nutrition to toddlers in order to reduce the risk of this case because it will have a significant impact on the next phase of life.